2006
DOI: 10.1186/1475-2875-5-85
|View full text |Cite
|
Sign up to set email alerts
|

Human malarial disease: a consequence of inflammatory cytokine release

Abstract: Malaria causes an acute systemic human disease that bears many similarities, both clinically and mechanistically, to those caused by bacteria, rickettsia, and viruses. Over the past few decades, a literature has emerged that argues for most of the pathology seen in all of these infectious diseases being explained by activation of the inflammatory system, with the balance between the pro and anti-inflammatory cytokines being tipped towards the onset of systemic inflammation. Although not often expressed in ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(217 citation statements)
references
References 327 publications
(383 reference statements)
11
195
2
9
Order By: Relevance
“…Parasitised red cells also block deep visceral capillaries by its attachment with endothelium and leads to lactic acidosis in severe falciparum malaria (Jarvis et al 2006;Planche and Krishna 2006) It is well known that coagulation system, being a cascade of enzymatically driven activity, does not function very well in the presence of acidosis. Table 1 Biochemical changes and changes in cytokine production in falciparum malarias (Clark et al 2006) Cytokine production in falciparum malarias Change(s) Cytokine storm deranging the coagulation system Several workers have studied the pattern of cytokine imbalance as a consequence of severe falciparum malaria (Day et al 1999;Chaiyaroj et al 2004). Table 1 presents a list of cytokines which get dysregulated in this disease (Troye-Blomberg et al 1983).…”
Section: Activation Of Coagulation By Parasitised Red Cellsmentioning
confidence: 98%
“…Parasitised red cells also block deep visceral capillaries by its attachment with endothelium and leads to lactic acidosis in severe falciparum malaria (Jarvis et al 2006;Planche and Krishna 2006) It is well known that coagulation system, being a cascade of enzymatically driven activity, does not function very well in the presence of acidosis. Table 1 Biochemical changes and changes in cytokine production in falciparum malarias (Clark et al 2006) Cytokine production in falciparum malarias Change(s) Cytokine storm deranging the coagulation system Several workers have studied the pattern of cytokine imbalance as a consequence of severe falciparum malaria (Day et al 1999;Chaiyaroj et al 2004). Table 1 presents a list of cytokines which get dysregulated in this disease (Troye-Blomberg et al 1983).…”
Section: Activation Of Coagulation By Parasitised Red Cellsmentioning
confidence: 98%
“…Haemophagocytosis in occasional patients may cause significant anemia and cytopenia in a small subset of patients with malarial infection (Ohno et al 1996;Clark et al 2006). It is not clearly known whether in these patients there is underlying immunodeficiency or EB virus infection to drive the haemophagocytosis or if it is because of inappropriate secretion of cytokines like TNF-α in the background of proper genetic background of the host.…”
Section: Haemophagocytic Syndromementioning
confidence: 99%
“…However, there is also significant underproduction of IL-10 and IL-12. Severe anemia in malaria is usually associated with low levels of IL-10 and IL-12 (Weatherall et al 2002;Harpaz et al 1992), Othoro et al 1999;Perkins et al 2000;Clark et al 2006), and it is believed that these cytokines may have some therapeutic application in severe malarial anemia.…”
Section: Cytokine Dysregulation In Malarial Infectionmentioning
confidence: 99%
“…This immunoregulation does not appear to have impaired the ability of animals to clear parasites but may have attenuated some malaria-associated pathology, such as reduced immune-mediated RBC lysis of uninfected erythrocytes. Studies in Senegal, Ghana, and elsewhere have suggested a more anti-inflammatory environment in groups protected from severe malaria (24,(61)(62)(63)(64)(65). Thus, an early proinflammatory response may be important in controlling parasitemia.…”
Section: Figmentioning
confidence: 99%
“…In Mali, low parasite density and delay in the first clinical symptoms were reported in the coinfected group (16), and in Thailand a similar group was protected from cerebral malaria (14). Protection against malaria parasitemia and disease requires both humoral and cellular immune responses, striking a balance between effector and immunoregulatory responses (59)(60)(61). There was no difference in cytokine production to crude S. mansoni or P. knowlesi antigens between the experimental groups, suggesting that adaptive immunity was unlikely to be involved.…”
Section: Figmentioning
confidence: 99%